Lettere 1936-1963 - Dessì, Giuseppe (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2012)
Author of Architettura del medioevo in Sardegna which won him the Premio Nazionale Olivetti in 1956, Raffaello Delogu was an art historian and Commissioner for Antiquities and Monuments in Sardinia, Abruzzo and Sicily. His correspondence with one of the most eminent Italian writers of the second half of the twentieth century, as transcribed and lavishly annotated here by Monica Graceffa, reveals him not only as a committed intellectual devoted to the study of ancient and modern art, but also as a caustic and playful friend. His dialogue with Giuseppe Dessí commenced in their youth, when Dessí was an amateur painter on the way to maturity, who instead rapidly developed into a mature writer and attentive connoisseur of all forms of art. In addition to their studies and mutual friends (including Claudio Varese and Maria Lai), they also shared an interest in painting and in what Dessí was experiencing (his moves, his political passion) and what he was writing (fiction, drama, essays); important in this regard are the letters touching on the collaboration of both on the Sardinian issue of Pietro Calamandrei's «Il Ponte».